The proper operation of the high vacuum pumping system - Gasperič, Jože (Kovine zlitine tehnologije, 1997)
The proper operation of high vacuum pumping system with oil diffusion pumps and backing rotary pumps is very important, otherwise the contamination of vacuum chambers by backstreaming oil vapours is extremely high as well as the oxidation and the loss of diffusion pump oil. The forepressure switching point, where the diffusion pump is put into the operation by opening the high vacuum and forepressure valves is discussed. There are three possible situations: the pumping throughput is just adapted, or it is too low or too high. What is going on, when the pumping throughput is adapted, it is ilustrated using the throughput-pressure diagram. At the end some practical advices are done, how to recognize that the operation of the HV pumping system is correct.
Keywords: črpalke; difuzijske črpalke; rotacijske črpalke; delovanje; nizki tlak